Eight novel hepatitis C virus genomes reveal the changing taxonomic structure of genotype 6. - Wang, H; Yuan, Z; Barnes, E; Yuan, M; Li, C; Fu, Y; Xia, X; Li, G; Newton, P; Vongsouvath, M; Klenerman, P; Pybus, O; et al. (2013)
Analysis of partial hepatitis C virus sequences has revealed many novel genotype 6 variants that cannot be unambiguously classified, which obscure the distinctiveness of pre-existing subtypes. To explore this uncertainty, we obtained genomes of 98.0-98.8% full-length for eight such variants (KM35, QC273, TV257, TV476, TV533, L349, QC271 and DH027) and characterized them using phylogenetic analyses and per cent nucleotide similarities. The former four are closely related phylogenetically to subtype 6k, TV533 and L349 to subtype 6l, QC271 to subtypes 6i and 6j, and DH027 to subtypes 6m and 6n. The former six defined a high-level grouping that comprised subtypes 6k and 6l, plus related strains. The threshold between intra- and inter-subtype diversity in this group was indistinct. We propose that similar results would be seen elsewhere if more intermediate variants like QC271 and DH027 were sampled.